A two-stage combined trickle bed reactor/biofilter for treatment of styrene/acetone vapor mixtures - Vanek, Tomas; Halecky, Martin; Paca, Jan; Zapotocky, Lubos; Gelbicova, Tereza; Vadkertiova, Renata; Kozliak, Evguenii; Jones, Kim (Journal of environmental science and health. Part A, Toxic/hazardous substances and environmental engineering, 2015)
Performance of a two-stage biofiltration system was investigated for removal of styrene-acetone mixtures. High steady-state acetone loadings (above C(in)(Ac) = 0.5 g.m(-3) corresponding to the loadings > 34.5 g.m(-3).h(-1)) resulted in a significant inhibition of the system's performance in both acetone and styrene removal. This inhibition was shown to result from the acetone accumulation within the upstream trickle-bed bioreactor (TBR) circulating mineral medium, which was observed by direct chromatographic measurements. Placing a biofilter (BF) downstream to this TBR overcomes the inhibition as long as the biofilter has a sufficient bed height. A different kind of inhibition of styrene biodegradation was observed within the biofilter at very high acetone loadings (above C(in)(Ac) = 1.1 g.m(-3) or 76 g.m(-3).h(-1) loading). In addition to steady-state measurements, dynamic tests confirmed that the reactor overloading can be readily overcome, once the accumulated acetone in the TBR fluids is degraded. No sizable metabolite accumulation in the medium was observed for either TBR or BF. Analyses of the biodegradation activities of microbial isolates from the biofilm corroborated the trends observed for the two-stage biofiltration system, particularly the occurrence of an inhibition threshold by excess acetone.
Keywords: Acetone; Bioreactors; aceton; plyny; styren; Bacteria; Filtration; Styrene; Gases; biofilmy; bioreaktory; filtrace; Biodegradation, Environmental; biodegradace; Biofilms